2021
DOI: 10.3390/ph14121309
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Icariin-Loaded Bilosome-Melittin Formulation with Improved Anticancer Activity against Cancerous Pancreatic Cells

Abstract: Pancreatic cancer currently represents a severe issue for the entire world. Therefore, much effort has been made to develop an effective treatment against it. Emerging evidence has shown that icariin, a flavonoid glycoside, is an effective anti-pancreatic cancer drug. Melittin, as a natural active biomolecule, has also shown to possess anticancer activities. In the present study, with the aim to increase its effectiveness against cancerous cells, icariin-loaded bilosome-melittin (ICA-BM) was developed. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A remarkable improvement in the cytotoxic activity of the compound 4e from PEGylated nanovesicle (IC 50 = 0.75 ± 0.03 µM) was found compared to the pure form (IC 50 = 2.11 ± 0.19 µM) [ 79 ]. In another study, Alhakamy et al [ 80 ] developed and evaluated icariin-loaded bilosomes-melittin (ICA-BM) in an attempt to increase the efficacy of these natural biomolecules against pancreatic cancer cells, PNAC1. The evaluation of pro-apoptotic protein levels, cell cycle analysis, and annexin V staining in PNAC1 cells demonstrated that the optimized ICA-BM formulation significantly augmented icariin’s efficacy in combating malignant pancreatic cells [ 80 ].…”
Section: Bilosomes As Nanocarrier Drug Delivery System For Treating V...mentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable improvement in the cytotoxic activity of the compound 4e from PEGylated nanovesicle (IC 50 = 0.75 ± 0.03 µM) was found compared to the pure form (IC 50 = 2.11 ± 0.19 µM) [ 79 ]. In another study, Alhakamy et al [ 80 ] developed and evaluated icariin-loaded bilosomes-melittin (ICA-BM) in an attempt to increase the efficacy of these natural biomolecules against pancreatic cancer cells, PNAC1. The evaluation of pro-apoptotic protein levels, cell cycle analysis, and annexin V staining in PNAC1 cells demonstrated that the optimized ICA-BM formulation significantly augmented icariin’s efficacy in combating malignant pancreatic cells [ 80 ].…”
Section: Bilosomes As Nanocarrier Drug Delivery System For Treating V...mentioning
confidence: 99%
“…In another study, Alhakamy et al [ 80 ] developed and evaluated icariin-loaded bilosomes-melittin (ICA-BM) in an attempt to increase the efficacy of these natural biomolecules against pancreatic cancer cells, PNAC1. The evaluation of pro-apoptotic protein levels, cell cycle analysis, and annexin V staining in PNAC1 cells demonstrated that the optimized ICA-BM formulation significantly augmented icariin’s efficacy in combating malignant pancreatic cells [ 80 ]. Another study by the same research group evaluated piceatannol (PIC), an herbal polyphenolic compound with anti-cancercytotoxic activity, which was loaded into zein-modified bilosomes for treating lung cancer.…”
Section: Bilosomes As Nanocarrier Drug Delivery System For Treating V...mentioning
confidence: 99%
“…ICRN (C 33 H 40 O 15 , M w = 676.67) is a type of prenylated flavonoid, showing extensive bioactivities such as antioxidant [ 44 , 45 , 46 , 47 ], neuroprotective [ 48 , 49 , 50 , 51 , 52 ], and antitumor [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] behavior as well as anti-inflammatory responses [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and can be used to treat erectile dysfunction [ 69 , 70 , 71 , 72 ]. It appears it can improve the function of organs including bones and the heart [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%